Analysis of renewable resources in Central China under the "double carbon" strategy. (November 2022) - Yu, Xiaowei; Wang, Bin; Wang, Wei; Guo, Xinyang; Han, Jingzuo; Chen, Xinyu
Abstract: China has proposed the ambitious target of peaking the carbon emissions by 2030 and realizing the carbon neutrality by 2060 (hereafter referred to as "double carbon" goal). Central China is supposed to be one of the most essential aspect for this target. However, renewable resources in the central China region encounter the issues of inferior capacity factor and restricted resource potential. A resource analysis for local onshore wind and solar PV is conducted here, incorporating inversion analysis data with high spatial and temporal resolutions (include wind field, surface radial, local elevation, slope and landscape), to propose the (1) spatial distribution and seasonal fluctuation of local onshore wind and solar PV; (2) supplied curves for all the provincial regions in Central China at every renewable investment level; (3) optimal provincial allocation and overall portfolio for local renewables in the Central China. This research is supposed to provide data and model support for the ongoing deployment of renewables in Central China, and the fulfillment of the "double carbon" goal in the entire country.